Flirting with fire - Porter, Jane, 1964- (Berkley Romance, 2023)
Swearing off New York, theater, actors-all of it-49-year-old Margot Hughes is thrown back into the theater world when she is tapped to take over a troubled summer production and finds unexpected love with her lead actor even though he represents everything she left behind.